1992
DOI: 10.1136/gut.33.10.1381
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to early mortality in cirrhotic patients bleeding from varices and treated by urgent sclerotherapy.

Abstract: Variceal haemorrhage in cirrhotic patients carries a high early mortality even when balloon tamponade or emergency sclerotherapy are applied. The aim of this study to identify patients dying within six weeks of their first variceal haemorrhage. One hundred and twenty one patients with parenchymal cirrhosis presenting with the first variceal bleeding episode between June 1983 and December 1988 were studied. Nineteen patients were excluded for various reasons. Emergency sclerotherapy was carried out in cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 17 publications
3
17
0
1
Order By: Relevance
“…Numerous attempts have been made to develop a reliable prognostic survival model for cirrhosis. The target population of the different scoring systems in the literature covers patients with liver cirrhosis [1-7], alcoholic liver disease [8,9], variceal bleeding [10-17], and upper gastrointestinal bleeding including variceal bleeding [18-20]. The Child-Turcotte classification [1] and its subsequent modification by Pugh [10] are old empiric methods to assess hepatocellular functional reserve in candidates for portosystemic shunting.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous attempts have been made to develop a reliable prognostic survival model for cirrhosis. The target population of the different scoring systems in the literature covers patients with liver cirrhosis [1-7], alcoholic liver disease [8,9], variceal bleeding [10-17], and upper gastrointestinal bleeding including variceal bleeding [18-20]. The Child-Turcotte classification [1] and its subsequent modification by Pugh [10] are old empiric methods to assess hepatocellular functional reserve in candidates for portosystemic shunting.…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors have been identified that are associated with mortality risk for an episode of AVH, including active bleeding at initial endoscopy, haematocrit level, aminotransferase levels, hepatic venous pressure gradient (HVPG), presence of portal vein thrombosis, alcoholic liver disease, serum bilirubin and albumin levels, hepatic encephalopathy, hepatocellular carcinoma (HCC) and the Child–Turcotte–Pugh (CTP) score 4 9. Many of these data have been derived from retrospective studies when mortality rates following an episode of variceal bleeding were up to 50%, from relatively small numbers of patients, or from patient groups in whom therapy was not according to a standard protocol, including variability in the use of antibiotics 4 10 11…”
mentioning
confidence: 99%
“…Many studies have focused on the search for predictors of mortality in cirrhotic patients, and their use to develop a reliable model of survival. In these studies, the study populations were cirrhotic patients [1]- [5], patients with alcoholic cirrhosis [6] [7], and cirrhotic patients after an episode of variceal bleeding [8]- [12]. The Child-Turcott score [1] and its subsequent modifications by Pugh [8] are old empirical methods used to assess the degree of liver failure in candidate patients for porto-systemic shunt.…”
Section: Introductionmentioning
confidence: 99%